Ответы и объяснения

  • Участник Знаний
2012-04-04T09:13:00+00:00

упростить выражения

1,5х+ 3(х+ 0,83) = 1,5х+ 3х+ 2,49 = 4,5х + 2,49

7,1+ 5(3,4 - х)= 7,1 + 17 - 5х = 24,1- 5х

Лучший Ответ!
2012-04-04T09:50:26+00:00

вот смотри и списывай на здоровье!!!!!!

Выражение: 7.1+5*(3.4-x)

Ответ: 24.1-5*x

Решаем по действиям:
1) 5*(3.4-x)=17-5*x
5*(3.4-x)=5*3.4-5*x
1.1) 5*3.4=17
X3.4
_ _5_
17
2) 7.1+17=24.1
+17.0
_ _7_._1_
24.1

Решаем по шагам:
1) 7.1+17-5*x
1.1) 5*(3.4-x)=17-5*x
5*(3.4-x)=5*3.4-5*x
1.1.1) 5*3.4=17
X3.4
_ _5_
17
2) 24.1-5*x
2.1) 7.1+17=24.1
+17.0
_ _7_._1_
24.1

 

 

а вот и второе!!!!!!!!!!!!!!!!!!!!!!!

Выражение: 1.5*x+3*(x+0.83)

Ответ: 4.5*x+2.49

Решаем по действиям:
1) 3*(x+0.83)=3*x+2.49
3*(x+0.83)=3*x+3*0.83
1.1) 3*0.83=2.49
X0.83
_ _ _3_ _
2.49
2) 1.5*x+3*x=4.5*x

Решаем по шагам:
1) 1.5*x+3*x+2.49
1.1) 3*(x+0.83)=3*x+2.49
3*(x+0.83)=3*x+3*0.83
1.1.1) 3*0.83=2.49
X0.83
_ _ _3_ _
2.49
2) 4.5*x+2.49
2.1) 1.5*x+3*x=4.5*x